Understanding the point mass balance and surface ice velocity for the debris-covered glacier, Panchi II, western Himalaya (India) - Sarvagya Vatsal; Mohd Farooq Azam; Anshuman Bhardwaj; Arindan Mandal; Raaj Ramsankaran; Mohd Soheb; Saumya G. Kutty; Chetan Singh; Somdutta Mishra; Alagappan Ramanathan; Ishmohan Bahuguna; Purvee Joshi; et al. (Results in Earth Sciences)
Debris-covered glaciers with complex morphological features, including ice cliffs and supraglacial lakes, remain relatively understudied in the Himalaya. Panchi II Glacier, located in the Bhaga Basin of the western Himalaya, exemplifies such complex debris-covered glacier. We conducted assessments of both the point mass balances and the surface ice velocity of the Panchi II Glacier. We measured the debris thickness at various elevation zones and observed non-uniformity in the debris thickness across the glacier. To understand the influence of debris thickness, our methodology encompassed the direct glaciological approach for point mass balance estimation, complemented by DGPS surveying and satellite-derived datasets for surface ice velocity estimation. The point mass balance for 2017–2021 indicates that debris thickness is a key factor in regulating glacier melt. Mean surface ice velocity of the whole glacier for the year 2019/21 was 9.2 ± 1.5 m a−1. Our findings indicate that for Panchi II Glacier melting is predominantly governed by debris thickness rather than elevation. Furthermore, multivariate linear analysis reveals that elevation, debris thickness, and slope explain 91 % variability in the surface ice velocity of the glacier.